1996
DOI: 10.3109/00365529609009132
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasound Measurement of Intestinal Blood Flow in Inflammatory Bowel Disease

Abstract: This study shows that Doppler US can demonstrate splanchnic hemodynamic changes in active IBD patients and, in particular, can be used to differentiate between active and quiescent UC. However, the assessment of CD activity by means of Doppler US requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 18 publications
5
44
2
2
Order By: Relevance
“…5 van Oostaynen et al studied the SMA only and found a significant diVerence between active and quiescent Crohn's disease both for flow volume and for RI. 6 9 In contrast, in a previous study of ours 7 we did not find differences between active and inactive Crohn's disease both for PV flow and V mean , for mesenteric vein flow and V mean , and for the RI of the SMA (flow volume of SMA was not evaluated). Furthermore, preliminary reports investigated SMA volume flow in patients with Crohn's disease and found that it was not sufficiently discriminatory for diagnostic purposes or for defining disease activity.…”
Section: Resistance Indexcontrasting
confidence: 49%
See 3 more Smart Citations
“…5 van Oostaynen et al studied the SMA only and found a significant diVerence between active and quiescent Crohn's disease both for flow volume and for RI. 6 9 In contrast, in a previous study of ours 7 we did not find differences between active and inactive Crohn's disease both for PV flow and V mean , for mesenteric vein flow and V mean , and for the RI of the SMA (flow volume of SMA was not evaluated). Furthermore, preliminary reports investigated SMA volume flow in patients with Crohn's disease and found that it was not sufficiently discriminatory for diagnostic purposes or for defining disease activity.…”
Section: Resistance Indexcontrasting
confidence: 49%
“…As previously reported the day to day variability of the measurements of PV and SMA parameters showed a Pearson correlation coeYcient no lower than 0.91 7 and the intraobserver variation had a coeYcient of variation of less than 10%.…”
Section: Evaluation Of Ultrasonography and Doppler Flowmetrymentioning
confidence: 51%
See 2 more Smart Citations
“…Standard transabdominal ultrasonography (US) has already been used for its diagnosis and clinical follow-up, [5][6][7] and, more widely, in a variety of other intestinal diseases, [8][9][10] including inflammatory bowel diseases. [11][12][13][14] Recent studies have highlighted neovascularization in the early stages of GVHD. 15 We previously reported our experience on the use of contrastenhanced ultrasound (CEUS) during I-aGVHD that showed contrast enhancement uptake in the bowel wall (BW).…”
Section: Introductionmentioning
confidence: 99%